ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERADAAN KOMITE MANAJEMEN RISIKO (STUDI EMPIRIS PADA PERUSAHAAN PERBANKANYANG TERDAFTAR DI BEI PERIODE 2012-2014) - Evind Glynis; Amries Rusli Tanjung; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This studied examines the effect of independent commisaries board, commisaries board size, external auditor reputation, financial reporting risk, leverage, firm size and audit committe characteristic on risk management committe. The sample of this study is 29 of banking companies that listed in BEI period 2012-2014. Analytical techniques used to perform the hypothesis testing is purposive sampling with secondary data. The Data got from website www.idx.com. Data are analyzed using logitic regression method using SPSS (Statistical Product and Service Solution) 17 version. The results showed variable independent commisaries board had effect on risk management committe with significance value of 0.035 and H1 accepted, commisaries board size had effect on risk management committe with significance value of 0.042 and H2 accepted, external auditor reputation had effect on risk management committe with significance value of 0.013 and H3 accepted, financial reporting risk had effect on risk management committe with significance value of 0.014 and H4 accepted, leverage had not effect on risk management committe with significance value of 0.553 and H5 rejected, firm size had effect on risk management committe with significance value of 0.022 and H6 accepted and audit committe characteristic had effect on risk management committe with significance value of 0.037 and H7 accepted.Keyword : management committee, independent commisaries, commisaries size, external auditor, financial risk, leverage, firm size, audit committe.